Translating the Restoring Body Image After Cancer (ReBIC) Group Therapy Intervention Into an Online Version: A Successful Case Study and Recommendations. Issue 3 (2nd July 2020) - Trachtenberg, Lianne; Wong, Jiahui; Rennie, Heather; Esplen, Mary Jane
ABSTRACT: A growing number of face-to-face group therapy interventions are being translated into online versions in psycho-oncology. Yet few researchers have systematically described the complex translation process or systematic approaches used to maintain the integrity of the original empirically supported interventions. In this article, we present a case study to illustrate the process of translating an evidence-based face-to-face therapy group, Restoring Body Image after Cancer (ReBIC) into an online format. We highlight how three critical therapeutic components from the original intervention (guided imagery exercises, psychoeducational reading materials, and psychotherapeutic group processes) were maintained and translated for online delivery. We provide preliminary recommendations for future translation efforts of text-based online group therapies to encourage best practices.